Indigenous Decolonization of Western Notions of Time and History through Literary and Visual Arts - Rose, Diana C.; Vuletic, Sne ana; Justus Liebig University Giessen (My University, 2018)
Since the early colonial period, indigenous peoples around the globe have been framed as being anchored in the past. The manner in which this was accomplished varied in different locations, yet it was all done with the same intent: to leave them outside of history. Placing indigenous peoples in the past meant assigning lesser value to their forms of life and thought than to those of the West, which allowed for all manner of injustices to be inflicted upon them. In response to this strategic misrepresentation, indigenous peoples reached for their own notions of history and time in an effort to validate an alternate perspective that could discredit the supremacy of dominant Western ideas. Thus, history and time become a highly contested terrain.In this essay, we explore some of the strategies used by two indigenous communities to decolonize Western representations of these groups. One of the case studies looks at how, in his 1958 novel Things Fall Apart, Igbo Anglophone writer Chinua Achebe deploys narrative time to challenge the Hegelian notion of sub-Saharan Africa as being outside of history. On the other side of the globe, contemporary Maya artists use their ancestral philosophies of time that included the coexistence of multiple temporalities, as a way to challenge the universality of Western ideas of progressive time, and thus of Western constructions of history. Through the literary and the visual, the Igbo and the Maya decolonize normative representations of time in their efforts to reinscribe their place in global history.
Keywords: decolonial; history; indigeneity; literary; time; visual; ddc:300